Effect of foliar application of nutrients on wheat (Triticum aestivum) crop performance, economics, resource use efficiency and soil properties under rainfed conditions - ABROL, VIKAS; SINGH, A P; KUMAR, ANIL; CHARY, RAVINDER; SRINIVASARAO, CH; SHARMA, PEEYUSH; SINGH, BRINDER; SALGOTRA, SANJEEV; KAPOOR, JAI; DADHICH, HEMANT (The Indian Journal of Agricultural Sciences, 2020)
Field studies were conducted during rabi season of 2015–16 to 2017–18 at research farm of Advanced Centre for Rainfed Agriculture, SKUAST-Jammu to study the effect of foliar application of nutrients on crop performance, economics, resource use efficiency and soil properties in wheat (Triticum aestivum. L). The experiment comprising seven treatments (viz. control, 0.5% K foliar spray (KNO3), 0.5% K foliar spray (KNO3) + 0.5% N foliar spray (Urea), 0.5% K foliar spray (KCl), 0.5% K foliar spray (KCl) + 0.5% N foliar spray (Urea), 0.5% N foliar spray (Urea), foliar spray of water) was laid out in randomized block design with three replications. Results revealed that all yield attributes, viz. plant height, number of tillers/m row, spike length, 1000 grain weight were significantly higher with foliar application than the other treatments. Highest grain (2198 kg/ha) and straw yield (3430 kg/ha) were obtained with foliar application of 0.5% K (KCl) + 0.5% N (urea) in addition to 100% RDF soil application (T5). Similarly, the maximum build up of soil organic carbon, available nitrogen, phosphorus and potassium, nutrient uptake, net return (₹ 29008 kg/ha) and B:C ratio (2.45) were recorded in T5 treatment. Significantly higher RWUE (19.49 kg/ha-mm), agronomic use efficiency (21.64 and 65.47) and apparent recovery of nitrogen and potassium (0.74 and 2.22) were observed in T5. The foliar application of 0.5% K (KCl) + 0.5% N (urea) in addition to 100% RDF had pronounced effect on soil properties, resource use efficiency, economics and crop performance of wheat under rainfed conditions.